1996
DOI: 10.3406/dreso.1996.1376
|View full text |Cite
|
Sign up to set email alerts
|

Justice de proximité et proximité de la justice. Les maisons de justice et du droit

Abstract: Sous des dehors très consensuels, la notion de « justice de proximité » recouvre aujourd'hui des contenus multiples. L'article se donne pour objectif de contribuer à en préciser la portée, à partir de l'analyse de l'activité des maisons de justice du Rhône. Qu'il s'agisse du traitement de la petite délinquance ou de l'accès au droit, l'observation des pratiques conduit à relativiser l'ampleur d'une proximité géographique. De même, la proximité humaine a tendance à s'effacer, au profit de l'avènement d'une prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
0
5
0
2
Order By: Relevance
“…They have been reluctant to enter the logic of partnerships which such a policy has presented, for fear of compromise and of losing their identity. With the MJD, they have been able to keep the initiative and preserve their own authority, while being seen to incorporate their own logic with an external societal preoccupation (Faget, 1997;Wyvekens, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been reluctant to enter the logic of partnerships which such a policy has presented, for fear of compromise and of losing their identity. With the MJD, they have been able to keep the initiative and preserve their own authority, while being seen to incorporate their own logic with an external societal preoccupation (Faget, 1997;Wyvekens, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The report was the result of the work of a commission and recommended the speeding up of penal matters and the expansion of victim/ offender mediation. Both in the report and in subsequent official policy documents three central dynamics can be discerned (Wyvekens, 1996(Wyvekens, , 1997a):…”
Section: The Genesis Of La Justice De Proximitémentioning
confidence: 99%
See 1 more Smart Citation
“…Several publications have examined whether the use of this concept has corresponded to any change in the way policies are implemented and whether the missions of the professions have been redefined. Wyvekens (1996Wyvekens ( , 1997 has described the transformations implied by the diffusion of justice de proximité. The most important of these is the growth of 'houses of justice', which are centres, often located in deprived urban areas that offer a range of services, including 'alternative' treatment of youth delinquency, usually through warnings or mediation, victim support and information about rights.…”
Section: The Banlieues and Rhetorics Of Proximitymentioning
confidence: 99%
“…Wyvekens found that initiatives of this kind, originally introduced because of external pressures on judicial institutions, had been instrumentalized: they were used by judicial institutions as a means of producing more 'efficient' ways of responding to juvenile delinquency without becoming substantially involved in local partnerships and thus preserving authority and independence. She further found that 'houses of justice', in which magistrates are involved, were marked by bureaucratization and the search for quicker answers to 'petty' delinquency (Wyvekens 1996(Wyvekens , 1997.…”
Section: The Banlieues and Rhetorics Of Proximitymentioning
confidence: 99%